Postdramatic Dramaturgies Resonances between Asia and Europe - Tuchmann, Kai (Pädagogik, 2022)
This book compiles lectures by the world's leading practitioners of postdramatic theatre from East Asia and the German-speaking world, which were given at Asia's only dramaturgy degree program at The Central Academy of Drama in Beijing 2018/19. It includes first-time English-language scripts of the discussed plays. The material is complemented by contextualizing essays by the program founder Li Yinan and its co-developer Kai Tuchmann. Hans-Thies Lehmann contributes the foreword to this volume. This rare compilation enables the reader to gain a unique insider's impression of postdramatic theatre's artistic thinking and working methods and informs about its manifold manifestations. With contributions from Hans-Werner Kroesinger, Lee Kyung-Sung, Li Yinan, Boris Nikitin, Kai Tuchmann, Wang Mengfan, Wen Hui, Zhao Chuan and Zhuang Jiayun.